Different Shelters to Domesticate Dwarf Snakehead (Channa limbata, Cuvier 1831) From the Progo River, Magelang, Central Java - Mujtahidah, Tholibah; Hidayati, Sri; Jailani, Abdul Qadir; Sari, Annisa Novita; Aji, Muhammad Tri; Armando, Eric (Department of Aquaculture, 2024)
This study's main focus is how the adaptation level affects the treatment of shelter composition in controlled containers. Parameters observed included growth rate, stress level, fish survival rate, and water quality during rearing. The research design used a completely randomized design (CRD) and was analyzed using SPSS. The results showed that the shelter composition was good for the C. limbata survival in experimental group 3 (P3) by placing the addition of sand, stones, gutters and aquatic plants in the aquarium. The effect of the composition of the shelter in a controlled container on the adaptation level of C. limbata was shown in experimental group 3 (P3), which experienced an increase in length of up to 5 mm, and an increase in weight of 25 g and a survival rate of 60%. This value is the best among 1st, 2nd, and control. This shows that the C. limbata can adapt its life to an artificial habitat that is as suitable as its natural habitat.